2001
DOI: 10.1046/j.1365-2842.2001.00839.x
|View full text |Cite
|
Sign up to set email alerts
|

Bruxism is mainly regulated centrally, not peripherally

Abstract: Bruxism is a controversial phenomenon. Both its definition and the diagnostic procedure contribute to the fact that the literature about the aetiology of this disorder is difficult to interpret. There is, however, consensus about the multifactorial nature of the aetiology. Besides peripheral (morphological) factors, central (pathophysiological and psychological) factors can be distinguished. In the past, morphological factors, like occlusal discrepancies and the anatomy of the bony structures of the orofacial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
316
1
58

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 454 publications
(388 citation statements)
references
References 38 publications
13
316
1
58
Order By: Relevance
“…Within the methodological limitations of the study, the conclusion of Kato et al [1] was that self-reported SB is associated with age, independent of tooth loss. This result is in accord with the theory that SB is mainly centrally mediated, not peripherally [4]. The state of the art today is that despite the fact that the aetiology of sleep bruxism seems to be multifactorial (sleep homeostasis and arousal activity, oromotor excitability, psychological and personality traits, genetics, neurochemical activities, and oropharyngeal functions), there is no evidence of the role of occlusal or other morphological factors [7].The finding of the current study that the prevalence of SB decreased with age was in accordance to similar studies performed all over the world, but for the first time this association was not confounded by tooth loss [1].…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Within the methodological limitations of the study, the conclusion of Kato et al [1] was that self-reported SB is associated with age, independent of tooth loss. This result is in accord with the theory that SB is mainly centrally mediated, not peripherally [4]. The state of the art today is that despite the fact that the aetiology of sleep bruxism seems to be multifactorial (sleep homeostasis and arousal activity, oromotor excitability, psychological and personality traits, genetics, neurochemical activities, and oropharyngeal functions), there is no evidence of the role of occlusal or other morphological factors [7].The finding of the current study that the prevalence of SB decreased with age was in accordance to similar studies performed all over the world, but for the first time this association was not confounded by tooth loss [1].…”
supporting
confidence: 92%
“…It was believed that occlusal interferences cause a reflex-mediated activation of the elevator muscles through the stimulation of periodontal mechanoreceptors. Accordingly, the role of the bruxism activity is to eliminate occlusal interferences [4]. If this theory was true, bruxism must stop with dental loss.…”
mentioning
confidence: 99%
“…Com isso, para que fossem afastadas variáveis que pudessem influenciar o padrão de realização do hábito parafuncional em questão, as participantes deste estudo não deveriam apresentar qualquer tipo de doença sistêmica (LOBEZOO; NAEIJE, 2001) (como diabetes, artrite, fibromialgia e outras). Também foi restringido o uso das medicações tais quais inibidores seletivos da receptação de serotonina, catecolaminas, anfetaminas, dopaminas, cafeína, antidepressivos tricíclicos, fenilalanina, agonista da serotonina, antipsicóticos e ansiolíticos (como os Benzodiazepínicos), além de relaxantes musculares uma vez que algumas drogas, principalmente as que atuam no âmbito do Sistema Nervoso Central, são capazes tanto de exacerbar o bruxismo -quadro conhecido como distonia induzida por drogas, sendo este tipo de bruxismo uma desordem distinta do de origem idiopática (ORTEGA, 2009), quanto atenuar os quadros do mesmo (LOBEZOO;NAEIJE, 2001;ORTEGA, 2009). Como o desgaste dentário pode estar presente também durante a realização de tratamentos ortodônticos (GRECHI et al, 2008), contraindicou-se a realização conjunta com o período da pesquisa em questão, assim como terapia para DTM.…”
Section: Discussionunclassified
“…Among them, dopamine is of special interest since abnormal oral movements have been observed in complex disorders associated to dopamine imbalance [2]. Interestingly, oral movements seem to be influenced by dopamine receptors agonist or antagonist [2,24]. Oral dyskinesias [26,29], and possibly nocturnal bruxism, a motor dysfunction characterized by clenching or grinding of the dentition during sleep states [23], have been associated with dopaminergic dysfunction [24,34].…”
Section: Conclusãomentioning
confidence: 99%
“…Interestingly, oral movements seem to be influenced by dopamine receptors agonist or antagonist [2,24]. Oral dyskinesias [26,29], and possibly nocturnal bruxism, a motor dysfunction characterized by clenching or grinding of the dentition during sleep states [23], have been associated with dopaminergic dysfunction [24,34]. Moreover, the consumption of drugs that alter dopaminergic transmission such as cocaine and amphetamine can cause intense tooth grinding in humans [3].…”
Section: Conclusãomentioning
confidence: 99%